2020
DOI: 10.24198/jkg.v32i2.27466
|View full text |Cite
|
Sign up to set email alerts
|

<p>Potensi ekstrak daun singkong (Manihot esculenta Crantz) terhadap ekspresi MMP-8 fibroblas gingiva pada model tikus dengan disfungsi ovarium dan periodontitis</p><p>Potential of cassava (Manihot esculenta Crantz) leaf extract on the MMP-8 expression of gingival fibroblast in rats model with ovarian dysfunction and periodontitis</p>

Abstract: Pendahuluan: Disfungsi ovarium merupakan kondisi yang menimbulkan defisiensi hormon estrogen dan progesteron. Penurunan hormonal ini menyebabkan peningkatan produksi tumor necrosis factor (TNF) yang dapat memicu peningkatan produksi matriks metalloproteinase-8 (MMP-8). Periodontitis yang disebabkan oleh bakteri gram negatif akan memicu makrofag melepaskan TNF-α yang berkontribusi dalam pembentukan MMP-8. MMP-8 ini berperan dalam degradasi kolagen jaringan ikat gingiva. Meningkatnya MMP-8 dapat menyebabkan terj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Decreased levels of these cytokines will speed up the healing process and increase fibroblasts quantity and collagen density. 29 Another study showed that surgically induced skin wounds in rats could be successfully treated with cassava leaf extract. Arranging connective tissue in a parallel pattern to collagen fibers accelerated the remodeling phase by several steps.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of these cytokines will speed up the healing process and increase fibroblasts quantity and collagen density. 29 Another study showed that surgically induced skin wounds in rats could be successfully treated with cassava leaf extract. Arranging connective tissue in a parallel pattern to collagen fibers accelerated the remodeling phase by several steps.…”
Section: Discussionmentioning
confidence: 99%
“…Cassava leaves extract containing bioactive compounds might have antioxidant activity. Our previous study revealed that the active ingredients, such as vitamins C, E, polyphenols, and flavonoids, were identified in the cassava leaf extract [15]. The cassava leaves extract acting as an exogenous antioxidant might balance the excessive oxidants caused by P. gingivalis infection.…”
Section: Discussionmentioning
confidence: 99%
“…It was stirred twice every 24 hours. The solution was concentrated with a rotary evaporator at 50 0 C and 90 rpm until the solution was semi-solid [15].…”
Section: Cassava Leaves Extract Preparationmentioning
confidence: 99%
See 2 more Smart Citations